Dreifältig eine? Zur Konstruktion von Regionalität im Dreiländereck Deutschland-Belgien-Niederland - Pohle, Frank (Gedächtnistopografien in Grenzräumen. Das Pommernland, Danzig und das Rheinland als trilaterale Kulturregionen, 2022)
Keywords: Belgien; Deutschland; Dreiländereck; Grenzgebiet; Regionale Identität; Regionalkultur; Rheinland

Secondary labour force of permanent staff? Foreign workers in the Aachen coal mines - Klank, Kristin (TSEG - The Low Countries Journal of Social and Economic History, 2008)
Abstract: „The paper gives an overview of the recruitment and professional status of workers in the coal mining district of Aachen from different origins, i.e. local miners, miners from other German coal districts, cross-border commuters from Dutch South-Limburg and labour migrants. Migration history generally assumes that foreign workers were primarily employed as temporary workers in workplaces abandoned by the local population. This article argues that the labour market situation of foreign commuters and labour immigrants has to be studied separately. Commuters were primarily skilled miners, who came to the mines on their own account. After the First World War, labour mobility between the Aachen region and South-Limburg was ephemeral and often resulted from sudden institutional changes. In general, long distance labour migrants were unskilled. They arrived in the mines in large groups hired directly by agents of the mines or mediated by the Federal Employment Office. The position of foreign immigrants underwent important changes. During the first recruitment drives of the Aachen mines between 1906 and 1912, immigrants were indeed considered as temporary workers; after the Second World War, the companies tried hard to make these workers stay beyond the minimal period of one year. Long-term labour contracts could lead to integration of immigrant workers into the permanent workforce, but also penalised workers who wished to leave prematurely.“
Keywords: Aachen (Region); Arbeitsmigration; Niederländer; Steinkohlenbergbau; Südlimburg (Niederlande)

Vaals en het drielandenpunt. De geschiedenis van een grensgebied - Janssen, Roger (Aprilis, 2007)
Keywords: Dreiländereck; Vaals

Das Problem der deutsch-belgischen Grenze in der Politik der letzten 150 Jahre - Pabst, Klaus (Zeitschrift des Aachener Geschichtsvereins, 1965)
Keywords: Staatsgrenze; deutsch-belgische Beziehungen